2017
DOI: 10.1007/s00401-017-1726-6
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis-like superoxide dismutase 1 proteinopathy is associated with neuronal loss in Parkinson’s disease brain

Abstract: Neuronal loss in numerous neurodegenerative disorders has been linked to protein aggregation and oxidative stress. Emerging data regarding overlapping proteinopathy in traditionally distinct neurodegenerative diseases suggest that disease-modifying treatments targeting these pathological features may exhibit efficacy across multiple disorders. Here, we describe proteinopathy distinct from classic synucleinopathy, predominantly comprised of the anti-oxidant enzyme superoxide dismutase-1 (SOD1), in the Parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
115
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 67 publications
6
115
0
Order By: Relevance
“…These including superoxide dismutase‐1 (itself having impaired function in Parkinson's disease; Trist et al . ), DJ‐1 (Biosa et al . ) (also involved in 20S‐proteasome regulation; Moscovitz et al .…”
Section: Discussionmentioning
confidence: 99%
“…These including superoxide dismutase‐1 (itself having impaired function in Parkinson's disease; Trist et al . ), DJ‐1 (Biosa et al . ) (also involved in 20S‐proteasome regulation; Moscovitz et al .…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we can then narrow the scope of future proteomic studies targeting these specific subcellular compartments using high-throughput shotgun proteomics methods, 33 which are currently underway in our laboratory. In addition, as both a-synuclein and SOD1 are demonstrated to aggregate in Parkinson’s disease, 34 determining the subcellular fraction where these metal changes occur allows us to then identify whether these alterations are associated with the soluble forms of these proteins, or the aggregated form which would reside in the insoluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The insoluble fraction of the Parkinson’s disease SN is also likely to include a smaller proportion by mass of small insoluble proteinaceous deposits, including Lewy bodies 24 and SOD1 aggregates. 34 While metals have been suggested to induce α-synculein oligomerisation and aggregation in vitro , 38 it is unclear whether Lewy bodies retain metal ions. We recently demonstrated that SOD1 aggregates recently identified in Parkinson’s disease share pathological similarities with the deposited protein in familial amyotrophic lateral sclerosis spinal cord and SN, 34 and this class of aggregate has been shown to be deficient in Cu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations